E-Entrepreneurship for E-Startups: Potentials, Common Challenges and Way Forward - Islam, Mohammad Aminul; Alghobiri, Mohammed A (Information Management and Business Review, 2019)
In today’s economic world, the advancement in technology has opened up new forms of economic activities, particularly business. Whilst entrepreneurship is a major factor in business, e-entrepreneurship has become a buzzword facilitated by the rapid advancement of internet and developments in Information and Communication Technologies (ICTs). E-entrepreneurship, in the name of transforming business from the local marketplace to the global one, has revolutionized the entire business processes. This set of new business mechanism has created new opportunities for the startups, which in this regard is termed as e-startups. The purpose of this paper, therefore, is to develop a comprehensive understanding of the concept of eentrepreneurship by addressing related potentials and challenges. Extant literature has been reviewed to this end. The analysis indicated that flexibility of and accessibility to technology and products, less capital and risk in comparison to physical businesses are the major advantages that an e-entrepreneur might enjoy while commencing an e-startup. On the other hand, lack of institutional support, digital security threat, tough competition with established brands, less innovation and lack of academic and practical exposure in terms of business and marketing are some barriers that challenge the operation of e-startups. The conclusion of the paper draws on some recommendations accordingly.